The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/fishes8060306
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of the Ecology and Conservation of Pseudoplatystoma Catfishes in the Neotropics

Abstract: Species of the genus Pseudoplatystoma, the long-whiskered catfishes, are important in commercial and recreational fisheries in South America, and some species have become key to regional aquaculture. Some species of the genus are under pressure due to overfishing and the negative impacts of dams. Six questions are asked in this review: (i) What species are in the genus, and where are they distributed? (ii) What are the life histories and ecologies of Pseudoplatystoma species? (iii) What are the patterns of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Our findings showed that females exhibit a higher sex ratio, length, and weight compared to P. punctifer males. The dominance or size structure of individuals in one sex over the other may be related to differential individual growth rates and early gonad maturation (Pereira et al, 2023;Suzuki et al, 2013). However, females invest significantly more effort in reproductive development compared to males (Barneche et al, 2018;Freitas & Montag, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that females exhibit a higher sex ratio, length, and weight compared to P. punctifer males. The dominance or size structure of individuals in one sex over the other may be related to differential individual growth rates and early gonad maturation (Pereira et al, 2023;Suzuki et al, 2013). However, females invest significantly more effort in reproductive development compared to males (Barneche et al, 2018;Freitas & Montag, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hydroelectric dams can cause deleterious consequences for fish populations, including the surubim, as they prevent reproductive migrations, and reduce individual biomass and spawning potential, reflecting negatively on the recruitment of natural stocks and fisheries productivity (Andrade et al, 2019;Pereira et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One species for which no studies have investigated the effects of interannual variability in flood pulses on growth is Pseudoplatystoma fasciatum. This catfish species transports nutrients and connects habitats through migration [31,32]. It is also a source of food security and income for riverine people in the Amazon basin.…”
Section: Introductionmentioning
confidence: 99%
“…This species is heavily fished and may be threatened by the growing construction of hydropower dams [33]. P. fasciatum is distributed in four countries of the Amazon basin, including the Amazon mainstem and the Madeira, Solimões, and Tapajós tributary rivers [31]. Understanding how interannual variability in flood pulses affects its growth is key to managing and conserving it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation